No improvement noted in overall or cause‐specific survival for men presenting with metastatic prostate cancer over a 20‐year period. Issue 6 (20th November 2013) - Wu, Jennifer N.; Fish, Kari M.; Evans, Christopher P.; deVere White, Ralph W.; Dall'Era, Marc A.
Abstract : BACKGROUND: Prostate cancer mortality in the United States has declined by nearly 40% over the last 25 years. However, to the authors' knowledge, the contribution of prostate‐specific antigen (PSA) screening for the early detection of prostate cancer remains unclear and controversial. In the current study, the authors attempted to determine whether improvements in survival over time among patients with metastatic prostate cancer have contributed to the decline in mortality. METHODS: Men aged ≥ 45 years who presented with de novo metastatic prostate cancer from 1988 to 2009 were identified within the California Cancer Registry. Overall survival and disease‐specific survival were estimated using the Kaplan‐Meier method. A multivariate analysis with Cox proportional hazards modeling was performed to adjust for different distributions of variables between groups. RESULTS: A total of 19, 336 men presented with de novo metastatic prostate cancer during the study period. On multivariate analysis, overall survival was found to be better for men diagnosed from 1988 through 1992 and 1993 through 1998 than for men diagnosed in the most recent era (hazards ratio, 0.78; 95% confidence interval, 0.72‐0.85 [ P < .001] and HR, 0.79; 95% confidence interval, 0.74‐0.86 [ P < .001]). There was no improvement in disease‐specific survival observed when comparing the most contemporary men (those diagnosed between 2004 and 2009) with those diagnosed between 1988 and 1997. CONCLUSIONS: In this analysis of men presenting with de novo metastatic prostate cancer, no consistent improvement in overall or disease‐specific survival could be demonstrated over time. These data suggest that improvements in survival for patients with advanced disease have not contributed substantially to the observed drop in prostate cancer mortality over the PSA era and that stage migration secondary to PSA screening plays a more prominent role. Cancer 2014;120:818–823 . © 2013 American Cancer Society . Abstract : Using a population‐based cancer registry of men with de novo metastatic prostate cancer, the authors found no improvements in survival over time across the prostate‐specific antigen (PSA) era. After adjusting for differences in baseline covariates, there was even a suggestion of worsening overall survival for contemporary men compared with men diagnosed before the use of PSA screening.